Mining and Communities in Northern Canada History, Politics, and Memory - Sandlos, John; Keeling, Arn (Canadian History and Environment, 2015)
For indigenous communities throughout the globe, mining has been a historical forerunner of colonialism, introducing new, and often disruptive, settlement patterns and economic arrangements. Although indigenous communities may benefit from and adapt to the wage labour and training opportunities provided by new mining operations, they are also often left to navigate the complicated process of remediating the long-term ecological changes associated with industrial mining. In this regard, the mining often inscribes colonialism as a broad set of physical and ecological changes to indigenous lands. Mining and Communities in Northern Canada examines historical and contemporary social, economic, and environmental impacts of mining on Aboriginal communities in northern Canada. Combining oral history research with intensive archival study, this work juxtaposes the perspectives of government and industry with the perspectives of local communities. The oral history and ethnographic material provides an extremely significant record of local Aboriginal perspectives on histories of mining and development in their regions. With contributions by: Patricia Boulter Jean-Sébastien Boutet Emilie Cameron Sarah Gordon Heather Green Jane Hammond Joella Hogan Arn Keeling Tyler Levitan Hereward Longley Scott Midgley Kevin O'Reilly Andrea Procter John Sandlos Alexandra Winton